2012
DOI: 10.1021/es204681y
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Improving the Bio-Oil Quality by Catalytic Fast Pyrolysis of Heavy-Metal-Polluted Biomass: Take Copper (Cu) as an Example

Abstract: Heavy-metal-polluted biomass derived from phytoremediation or biosorption is widespread and difficult to be disposed of. In this work, simultaneous conversion of the waste woody biomass into bio-oil and recovery of Cu in a fast pyrolysis reactor were investigated. The results show that Cu can effectively catalyze the thermo-decomposition of biomass. Both the yield and high heating value (HHV) of the Cu-polluted fir sawdust biomass (Cu-FSD) derived bio-oil are significantly improved compared with those of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(68 citation statements)
references
References 49 publications
1
67
0
Order By: Relevance
“…The dried biomass was crushed using a high-speed rotary cutting mill, and the biomass with the particle size smaller than 120 mesh were collected. The proximate analysis and elemental composition of the biomass were determined and the results were reported in our previous work24.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dried biomass was crushed using a high-speed rotary cutting mill, and the biomass with the particle size smaller than 120 mesh were collected. The proximate analysis and elemental composition of the biomass were determined and the results were reported in our previous work24.…”
Section: Methodsmentioning
confidence: 99%
“…In our continuing efforts toward biomass waste disposal and resource recovery24252627, we have developed a rapid, low-cost, and readily scalable approach for synthesizing a magnetic porous carbonaceous solid acid catalyst (MPC–SO 3 H) by using biomass waste as a precursor. This method involves fast pyrolysis of Fe-preloaded biomass to produce MPC material; subsequent sulfonation of the obtained material is used to prepare a solid acid catalyst.…”
mentioning
confidence: 99%
“…There are many ways to improve the bio-oil quality including catalytic cracking, decarboxylation, decarbonylation, oligomerization and dehydrogenation with the assistance of various catalysts such as HZSM-5, Al-MCM-41, TiO 2 , ZrO 2 and Al 2 O 3 . 28 Liu et al 29 directly loaded Cu on sawdust biomass by impregnation method and found that the sawdust can be decomposed into small-molecular aromatics and the fractions of C 7 -C 10 compounds in the bio-oil are increased signicantly. They found that HZSM-5 shows the most effective in production of aromatic hydrocarbon from the pyrolysis of biomass when compared with other kinds of zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…Ni and Co catalysts were found more reactive than Fe but were deactivated faster [210]. Copper can effectively catalyse the thermodecomposition of biomass [211].…”
Section: The Gasification Of Biomass Feedstock Withmentioning
confidence: 96%